IMPLEMENTASI KEBIJAKAN KARTU JAKARTA SEHAT (KJS) DI DKI JAKARTA - Yessica .; Turtiantoro .; Achmad Taufiq (Journal of Politic and Government Studies, 2014)
Health is one of the primary needs for everyone so the need for health insurance. Health insurance basically aims to provide health services to the community because in reality many of the limitations of the poor to meet the primary needs that the government also intervened in this matter, as stipulated in Law No. 36 of 2009 Number of health states that the government is responsible for the willingness access to information, eduksi, and health care facilities for the community. So the Jakarta administration to make a health policy based on Jakarta Governor Decree No. 187 of 2012 About Acquisition Cost of Health Care named Jakarta Health Cards